2018
DOI: 10.3389/fmicb.2018.00966
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Trap Formation in Response to Trypanosoma cruzi Infection in Granulocytes Isolated From Dogs and Common Opossums, Natural Reservoir Hosts

Abstract: Granulocytes mediate the first line of defense against infectious diseases in humans as well as animals and they are well known as multitasking cells. They can mediate antimicrobial activity by different strategies depending on the pathogen they encounter. Besides phagocytosis, a key strategy against extracellular pathogens is the formation of extracellular traps (ETs). Those ETs mainly consist of DNA decorated with antimicrobial components and mediate entrapment of various pathogens. In the last years, variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…In this context, local pro-inflammatory responses in skin lesions in AAT, resulting in focal edema, were associated with PMN recruitment and granuloma formation surrounding T. b. brucei replication sites (10). PMN reacts against protozoan and metazoan parasites by different effector mechanisms which include the release of immunomodulatory molecules [e.g., cytokines, chemokines (CXCL1, CXCL8, CXCL10) (11,12)], phagocytosis, production of reactive oxygen species (ROS), and release of neutrophil extracellular traps (NETs) (11,13,14). So far, different parasite species were identified to induce either nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX)-dependent or NOX-independent NETs formation (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, local pro-inflammatory responses in skin lesions in AAT, resulting in focal edema, were associated with PMN recruitment and granuloma formation surrounding T. b. brucei replication sites (10). PMN reacts against protozoan and metazoan parasites by different effector mechanisms which include the release of immunomodulatory molecules [e.g., cytokines, chemokines (CXCL1, CXCL8, CXCL10) (11,12)], phagocytosis, production of reactive oxygen species (ROS), and release of neutrophil extracellular traps (NETs) (11,13,14). So far, different parasite species were identified to induce either nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX)-dependent or NOX-independent NETs formation (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the cells revealed a high percentage of eosinophils in the granulocyte fraction. Free extracellular DNA was detected after didelphine granulocytes were stimulated by T. cruzi [77]. The addition of cholesterol-depleting methyl-β-cyclodextrin (CD) also induced the release of extracellular traps, as has been previously shown in human [31] and bovine neutrophils [126], indicating a conserved role of lipid membrane composition in NET formation.…”
Section: Extracellular Traps In Didelphidaementioning
confidence: 59%
“…The study showed that ERK1/2, MAPK, and SOCE pathways were involved in the phenotype, and the parasites were entrapped within the NET structures [74]. Recently, two studies showed that canine PMNs also release extracellular traps in response to Trypanosoma cruzi [77] and Dirofilaria immitis microfilariae, and their L3 stage larvae [78]. Finally, also an overexposure to nickel in the form of nickel nitrate, a commonly used heavy metal material in battery manufacturing, triggered the release of extracellular traps from canine neutrophils [143].…”
Section: Extracellular Traps In Carnivores Such As Felidae Canidae mentioning
confidence: 99%
See 2 more Smart Citations